Developing Professionality In School - G Gunawan (UMSU, 2020)
The question of professionalization is still often questioned by people, but there are clear characteristics and detailed elements that are supportive of the understanding of professionalization. Likewise the teacher's position has been confirmed as an educational profession. Because it's only natural this profession gets its proper place in the middle of other professions. The education profession requires professional competence of teachers, which creates certification requirements and extensive experience which, among others, is obtained from teacher education institutions and quality teacher education programs, relevant to the needs of the field, and takes place on an ongoing basis.When local governments have a strong political will accompanied by policies that prioritize the importance of education as a human investment effort in the region, it is certain that the quality of education will be upheld. Conversely, if the regional government views education as not important, so that the vision and mission of education in the region is not clearly formulated and cannot be developed into a solid education fraction, it will be easy to guess that education in the region will not be good.As a result, education fractions will run unprofessionally, schools will be managed ineffectively. Finally, the vision and mission in the school will turn into something that is considered too luxurious. So this condition will encourage education fractions in the regions to lose their direction in carrying out their functions professionally. Keywords: Professionalism, School